A task design based review on eye-tracking studies within mathematics education - Bairral, Marcelo; Aldon, Gilles (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2024)
This paper presents a based review on Eye-Tracking (ET) studies in mathematical problem-solving. ET method provides a promising channel for educational researchers to connect learning outcomes to cognitive processes. Due to the advent of digital technologies, eye tracking studies are increasingly growing in different fields and in mathematics education. The main principle of eye tracking is that our gaze and our focus of attention are connected. If the task provided by the teacher is one of the ways to analyze cognitive processes, we wonder how ET studies are dealing with load cognitive on task design. We captured 39 papers, 23 of which were more specifically analyzed, based on mathematical proposed tasks in three intertwined strands: mathematical problem-solving, affective aspects and reasoning and proofs. We observed an expressive amount of low demand tasks on ET papers, the studies are still mainly based on numerical issues and focused less on geometry topics, and few of them are integrating digital technology on the provided tasks. Our didactical contribution is to claim for more high cognitive demand tasks regarding mathematical processes of thinking and geometrical learning.